Mycobacterium fortuitum empyema associated with an indwelling pleural catheter: Case report and review of the literature. Issue 3 (March 2017) - Blair, Paul; Moshgriz, Mahdi; Siegel, Marc
Abstract: Mycobacterium fortuitum is a rapidly growing mycobacterium (RGM) that is an uncommon cause of healthcare-associated infections. The most common infections caused by M. fortuitum include skin, soft tissue, and catheter-related infections. Although occasionally cultured from sputum samples, M. fortuitum is a rare cause of pulmonary disease. We report a case of M. fortuitum empyema associated with an infected pleural catheter and review M. fortuitum pulmonary infections.